Effect of yttria-doping on mechanical properties of bovine hydroxyapatite (BHA) - Gunduz, O.; Daglilar, S.; Salman, S.; Ekren, N.; Agathopoulos, S.; Oktar, F. N. (SAGE PUBLICATIONS LTD, 2008)
Sintered bodies of hydroxyapatite, derived from calcinated bovine bone (BHA) and doped with 0.5 and 1wt% Y2O3, were prepared. Measurements of density, compression strength, and microhardness, along with scanning electron microscopy (SEM) and X-ray diffraction (XRD) were carried out. The experimental results showed that BHA doping with yttria favors formation of glassy phase, which advances sintering and results in a dense and reinforced BHA matrix. The best mechanical properties were achieved after sintering at 1200 degrees C for compressive strength (82 MPa) and 1300 degrees C for microhardness (672 HV). These results are better than pure BHA or composites of hydroxyapatite with Y2O3-stablized zirconia, qualifying yttria (as dopant of BHA) for further in vitro and in vivo experimentation.
Keywords: hydroxyapatite; yttria; sintering; microstructure; mechanical properties; ZIRCONIA; ENAMEL; Materials Science